2003
DOI: 10.1177/147323000303100514
|View full text |Cite
|
Sign up to set email alerts
|

Ascorbic Acid Enhances Hypoxic Ventilatory Reactivity in Elderly Subjects

Abstract: The reducing properties of ascorbic acid in the carotid body make it a likely modifier of hypoxia-sensing mechanisms. This open-label study aimed to determine the effect of ascorbic acid on the hypoxic ventilatory response (HVR) in a population of elderly women, in whom both hypoxic reactivity and ascorbic acid levels may be deficient. We examined the HVR to progressive eucapnic hypoxia in 18 healthy females aged 60 -80 years, before and after 10 days' ascorbic acid supplementation, given as a sustained releas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
8
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 25 publications
1
8
1
Order By: Relevance
“…These findings imply an active role of the ascorbate moiety of AP in shaping the hypoxic responsiveness. The findings also conform to a human study in which the enhancement of hypoxic response to progressive hypoxia was noted in a population of elderly women after a period of supplementation with ascorbic acid [18].…”
Section: Discussionsupporting
confidence: 69%
“…These findings imply an active role of the ascorbate moiety of AP in shaping the hypoxic responsiveness. The findings also conform to a human study in which the enhancement of hypoxic response to progressive hypoxia was noted in a population of elderly women after a period of supplementation with ascorbic acid [18].…”
Section: Discussionsupporting
confidence: 69%
“…Putting our present and previous findings together, it seems that in resting conditions, in the absence of inhibiting factors, Aox may not alter carotid body output but may increase it when such factors are present. This could be important in elderly people (> 70 years): they have been reported to possess a considerably lower O 2 sensitivity than healthy young adults (Kronenberg & Drage, 1973; Peterson et al 1981), while in women 60–80 years of age ascorbic acid supplementation appeared to increase their hypoxic response (Pokorski & Marczak, 2003). The ability of antioxidants to alter the hypoxic response may vary between different reducing agents.…”
Section: Discussionmentioning
confidence: 99%
“…In older women with an age-related reduction of hypoxic sensitivity, ascorbic acid supplementation appeared to increase their hypoxic response (Pokorski & Marczak, 2003). Recently, we showed that an antioxidant mixture, consisting of oral α-tocopherol and intravenous ascorbic acid was able to reverse the reduction of the hypoxic response in humans by subanaesthetic concentrations of inhalational anaesthetics (Teppema et al 2002(Teppema et al , 2005.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…It does not appear, however, that in healthy younger adults the HVR is improved via antioxidants alone but rather in a depressed state (45). In elderly women, however, vitamin C was shown to enhance the HVR (36). It would therefore seem plausible that COPD patients may improve their HVR following an antioxidant intervention, secondary to increased diseaserelated ROS.…”
mentioning
confidence: 95%